Periodontitis A Useful Reference - Arjunan, Pachiappan (IntechOpen, 2017)
Periodontitis - A Useful Reference is a comprehensive book compiled by a team of experts with the objective of providing an overview of the basic pathology of "periodontitis" and its implication on oral health and general systemic health. Periodontitis has become a global health burden in recent days. It is noteworthy that oral health is being considered as the mirror of general health and the study of oral-systemic health connections has advanced among scientists, clinicians, and the public as well. We wish the array of chapters that highlights the importance and impact of periodontal health could be a useful guide for the community of public, students, and clinicians.